Arterial Embolization: Blood‐Derived Biomaterial for Catheter‐Directed Arterial Embolization (Adv. Mater. 52/2020). Issue 52 (28th December 2020) - Altun, Izzet; Hu, Jingjie; Albadawi, Hassan; Zhang, Zefu; Salomao, Marcela A.; Mayer, Joseph L.; Jamal, Leila; Oklu, Rahmi
Abstract : In article number 2005603, Rahmi Oklu and co‐workers introduce a novel blood‐derived growth‐factor‐rich nanocomposite hydrogel for endovascular embolization. This hydrogel can be rapidly prepared from blood for immediate use; also, it can be injected using clinical catheters, it is visible under fluoroscopy and has superior mechanical properties.